Surface engineering of nano magnesium alloys for orthopedic implants: a systematic review of strategies to mitigate corrosion and promote bone regeneration - Chaudhari, Yogesh Subhash; Chaudhari, Manisha Yogesh; Gholap, Amol D.; Alam, Mohammad Intakhab; Khalid, Mohammad; Webster, Thomas J.; Gowri, S.; Faiyazuddin, Md. (Frontiers in Bioengineering and Biotechnology, 2025)
Magnesium (Mg) alloys are transformative candidates for biodegradable orthopedic implants due to their bone-mimetic elastic modulus (10–30 GPa), biocompatibility, and osteogenic properties. However, rapid corrosion (>2 mm/year) and hydrogen gas evolution (0.1–0.3 mL/cm2/day) in physiological environments hinder clinical adoption. This systematic review, leveraging insights from seven databases (PubMed®, Embase, Web of Science™, Scopus®, IEEE Xplore, FSTA, and Google Scholar), critically evaluates surface engineering innovations that address these challenges. Key findings demonstrate that micro-arc oxidation (MAO) reduces corrosion rates by 60% (0.3–0.8 mm/year) through ceramic oxide layers, while hydroxyapatite (HA) coatings further enhance osteoconductivity (0.25 mm/year). Nanoscale MgO not only promotes osteoblast adhesion (40% increase) and collagen synthesis but also reduces bacterial colonization by 78% via surface energy modulation, eliminating antibiotic dependency. Advanced strategies like hybrid coatings (e.g., zwitterionic polymers) and alloying with Zn/Ca/Sr synergistically improve mechanical strength (up to 380 MPa), degradation control (0.1–0.5 mm/year), and angiogenesis via Mg2+-mediated VEGF upregulation. Emerging trends such as 4D bioprinting of pH-responsive Mg scaffolds and patient-specific implants highlight the shift toward dynamic, personalized solutions. Despite progress, challenges persist in synchronizing degradation with bone healing timelines, particularly in osteoporotic or diabetic patients. This review underscores the paradigm shift toward nano surface engineering, positioning Mg alloys as multifunctional platforms for next-generation orthopedic implants, while advocating for interdisciplinary collaboration to bridge translational gaps.